2014
DOI: 10.1002/mbo3.194
|View full text |Cite
|
Sign up to set email alerts
|

Arginine promotes Proteus mirabilis motility and fitness by contributing to conservation of the proton gradient and proton motive force

Abstract: Swarming contributes to Proteus mirabilis pathogenicity by facilitating access to the catheterized urinary tract. We previously demonstrated that 0.1–20 mmol/L arginine promotes swarming on normally nonpermissive media and that putrescine biosynthesis is required for arginine-induced swarming. We also previously determined that arginine-induced swarming is pH dependent, indicating that the external proton concentration is critical for arginine-dependent effects on swarming. In this study, we utilized survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 48 publications
2
20
1
1
Order By: Relevance
“…Arginine can be converted to ornithine by arginase. In the context of the other mutants identified in this study, arginine was previously found to increase c-di-GMP levels and perhaps via this pathway, this amino acid was observed to promote biofilm formation ( Chen et al, 2013 ) and alter swarming ( Sturgill and Rather, 2004 ; Bernier et al, 2011 ; Armbruster et al, 2013 , 2014 ). Consistent with the literature, in this study, the ADC/ODC mutant caused reduced biofilm formation and loss of flagella, however, the swarming motility was not affected ( Figures 3A,O,Z ; Supplementary Table S3 ).…”
Section: Discussionmentioning
confidence: 59%
“…Arginine can be converted to ornithine by arginase. In the context of the other mutants identified in this study, arginine was previously found to increase c-di-GMP levels and perhaps via this pathway, this amino acid was observed to promote biofilm formation ( Chen et al, 2013 ) and alter swarming ( Sturgill and Rather, 2004 ; Bernier et al, 2011 ; Armbruster et al, 2013 , 2014 ). Consistent with the literature, in this study, the ADC/ODC mutant caused reduced biofilm formation and loss of flagella, however, the swarming motility was not affected ( Figures 3A,O,Z ; Supplementary Table S3 ).…”
Section: Discussionmentioning
confidence: 59%
“…As non-swarming mutants are only capable of migrating across hydrogel-coated catheters, swarming is likely an important aspect of initial bladder colonization in catheterized individuals. Five cues that can induce swarming in P. mirabilis are present in human urine (arginine, glutamine, histidine, malate, and ornithine), and may contribute to swarm cell differentiation and migration across urine-bathed catheters as they promote swarming on urine agar plates (165, 317, 318) (Fig. 33).…”
Section: Virulence Factorsmentioning
confidence: 99%
“…that Hyf complex is similar to respiratory NADH dehydrogenase complex I 11,13,14 and the complex I was shown to provide the proton motive force (PMF) 31 , which could affect acid resistance, susceptibilities of polymyxin B and aminoglycosides, motility and growth under treatment of the PMF uncoupler [32][33][34][35][36][37] . We monitored the PMF- (Table 3; Fig.…”
Section: Loss Of Fhla or Hyf Does Not Affect Proton Motive Force-relamentioning
confidence: 99%